The Kind of Man I Am : Jazzmasculinity and the World of Charles Mingus Jr. - Rustin-Paschal, Nichole (Book collections on Project MUSE., 2017)
"Examines the effects of race and masculinity on both Charles Mingus Jr and the culture of jazz"--